Apuleius Madaurensis Metamorphoses, Book XI The Isis Book - Keulen, W; Egelhaaf-Gaiser, U; Harrison, S; al., E (Brill, 2014)
Using a transdisciplinary approach for a thorough assessment of the much-debated religious ending of the Metamorphoses, this new and detailed commentary on Apuleius' Isis book will elucidate the narrative in its literary, religious, ...